Fossil water disposal at oil and gas facilities - R. E. Shesterikova; E. A. Shesterikova; I. I. Shikhalieva; I. S. Shikhalieva (Вестник Северо-Кавказского федерального университета, 2022)
Iodine and its processing products are widely employed in human life. Formation water at an oil and gas facility could serve a raw stuff source for iodine. The advantage in this case is that there is no expenditure required that includes iodine production cost - water well drilling cost.